The Influence of Sustainability Reporting and Profitablity on Investor Trust in Manufacturing Companies Listed on the Indonesia Stock Exchange - Vanda Grace Novelia Ohee; Made Gede Wirakusuma (Harmony Management: International Journal of Management Science and Business, 2025)
The concept of Environmental, Social, and Governance (ESG) encourages companies to enhance transparency in disclosing their economic, social, and environmental performance through sustainability reporting, which is expected to increase accountability and serve as a positive signal to investors. In Indonesia, particularly in the manufacturing sector that contributes significantly to the economy while also generating environmental impacts, sustainability reporting practices have been expanding, although their effectiveness in building investor trust remains contested. This study aims to analyze the influence of sustainability reporting and profitability on investor trust in manufacturing companies listed on the Indonesia Stock Exchange (IDX), employing a quantitative method based on secondary data from annual and sustainability reports for the period 2020–2023. The sample was determined using purposive sampling, while the analysis was conducted through multiple linear regression with Price to Book Value (PBV) as a proxy for investor trust. The results indicate that, simultaneously, economic performance, environmental performance, social performance, and profitability significantly affect investor trust. However, partially, economic, environmental, and social performance show no significant effect on investor trust. In contrast, profitability exerts a positive and significant influence, making it the primary factor shaping investor trust. These findings suggest that investors in Indonesia still prioritize financial information over sustainability disclosures in making investment decisions.